PENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MATERI JARING-JARING BANGUN RUANG MELALUI PENERAPAN SCIENTIFIC APPROACH KELAS V SEMESTER 2 DI SDN 6 DAWUHAN SITUBONDO TAHUN AJARAN 2013/2014 - Nuris Hidayat; Amalia Risqi Puspitaningtyas (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2014)
In the learning process, there are several issues that developed, especially regarding the learning aims among others that when there are students who work on the problems when teacher ask student to work directly on board, discovered several errors in the process and the final chance to answer correctly, other students are less careful in observing only see the end result. Learning is still centered on teacher, therefore students just being a good listener and they acquire knowledge is transferred from a teacher so that concepts obtained is limited to fantasy not the result of the experience that the students themselves found in the learning process.It can be affected on the thinking process and learning outcomes (test scores daily) are still low. The problem is formulated as follows: 1) How can the application of Scientific Approach in Mathematics with learning material Nets Build Space on fifth grade students at SDN 2nd semester 6 Dawuhan Situbondo 2013/2014 school year, and 2) Does the application of the Scientific Approach can improve critical thinking and learning outcomes of fifth grade students in mathematics learning materials Nets Build space on SDN 2nd semester 6 Dawuhan Situbondo academic year 2013/2014. The results obtained in this study showed an increase of student’s critical thinking skills and student learning outcomes. At a critical capability in stage 1 cycle of 63% as many as 22 students who have mastery in the quiz. In stage 2 cycle by 83% as many as 29 students who have mastery in the quiz,therefore the study was discontinued. While in the pretest phase of learning outcomes by 45% as many as 16 students who have mastery. In cycle 1, the learning outcomes of students has increased to 68% as many as 24 students who have mastery learning in daily tests. From the pre-test stage 1 cycle to increase learning outcomes. In cycle 2, the learning outcomes of students has increased to 89% as many as 31 students who have mastery of learning outcomes that the study was discontinued. Based on these data,it can be conclude that the Scientific Approach able to improvethe critical thinking skills and student learning outcomes in build the nets space material in classrooms of SDN 6Dawuhan Situbondo. In this study, it proposed some suggestions as follows: The teacher of primary school should be able to utilize mathematical learning material webs wake-up space through learning scientific approach as an alternative to improve teaching strategies that have been used